Influence of the exposure concentration of dissolved cadmium on its organotropism, toxicokinetic and fate in Gammarus fossarum. (January 2023) - Gestin, Ophélia; Lacoue-Labarthe, Thomas; Delorme, Nicolas; Garnero, Laura; Geffard, Olivier; Lopes, Christelle
Graphical abstract: Highlights: The ku of all organs (except intestine) depend on the exposure concentration. The ke of all organs are not dependent on the exposure concentration. In vivo regulation of Cd remains the same depending on exposure concentrations. Intestine and gills are the two pathways for Cd uptake. Only intestine eliminates Cd to water, while gills play a key role in Cd storage. Abstract: Information on the relationship between the exposure concentrations of metals and their biodistribution among organs remained scarce in invertebrates. The objective of this study was to investigate the effects of Cd concentration on the organotropism, toxico-kinetic and fate of this metal in different organs of gammarids exposed to dissolved radioisotope 109 Cd. Gammarids male were exposed for 7 days to three environmental Cd concentrations (i.e. 4, 52 and 350 ng.L −1 ) before being placed in depuration conditions (i.e. uncontaminated water). At several sampling times, Cd concentrations were determined by 109 Cd γ-counting in water, caeca, cephalon, gills, intestine and remaining tissues. Bioconcentration Factors (BCF) and Cd relative proportions in organs were calculated to assess the exposure concentration effect on the bioaccumulation capacities. The dependance of the organ-specific kinetic parameters to Cd water concentrations were estimated by fitting nested one-compartment toxico-kinetic (TK) models to both the accumulation and depuration data, by Bayesian inference. Then, for each Cd concentrations, the metal exchanges among organs over time were formalized by a multi-compartments TK model fitted to all organ data simultaneously. Our results highlighted that, at the end of the exposure phase, BCF and Cd relative proportions, in each organ, were not significantly modulated by water concentrations. Kinetically, Cd accumulation rates in all organs (except intestines) were depended on the exposure concentration, but not the elimination rates. The in vivo management of Cd (i.e. metal exchanges among organs) remained qualitatively unchanged according to exposure concentration. All these results also highlighted key role of that organs in the management of Cd: bioconcentration by caeca, storage by gills and main entry pathway by intestine. This study shows the interest of implementing TK approaches to test the effect of environmental factors on bioaccumulation, inter-organ exchanges and fate of contaminants in invertebrate body to enhance the understanding of the toxicity risk.